Baricitinib in the Treatment of Patients with COVID-19: A Review of International Data and Analysis of Clinical Results in the Russian Population - А. I. Zagrebneva; Е. А. Baryakh; Е. I. Zhelnova; N. G. Poteshkina; I. Р. Beloglazova; Z. Yu. Mutovina; I. V. Samsonova; Е. А. Kovalevskaya; V. V. Parshin; V. V. Pshenichnikova; D S. Fomina; Т. S. Kruglova; et al. (Антибиотики и Химиотерапия, 2021)
The eﬀects of baricitinib, a selective reversible inhibitor of Janus kinase 1 and 2, in the treatment of COVID-19 are associated with diﬀerent aspects of pathogenesis — inhibition of viral endocytosis, reduction of excessive inﬂammatory response, and mitigation of vascular and pulmonary damage, which is a strong rationale for using baricitinib to treat patients with COVID-19. In the period from April to May 2020, City Clinical Hospital No. 52 obtained clinical experience of baricitinib clinical use in the therapy of 113 patients with COVID-19: 58 (51%) women and 55 (49%) men, whose average age was 57±12.6 years old. Analysis of the results of using baricitinib showed that therapy with baricitinib against the background of standard pathogenetic therapy was found to be eﬀective in 95 (84%) patients and ineﬀective in 18 (16%). Signiﬁcant positive changes were shown in comparison with the baseline level of the following indicators: body temperature (from 37.2±0.8˚C to 36, ±0.68˚C, P=0.000), blood oxygen saturation (from 95.5±3.0% to 96.5±2.2%, P=0.011), C-reactive protein (from 46.1±48.0 mg/L to 33.5±43.7 mg/L, P=0.010 ), National Early Warning Score (NEWS) (from 1.7±1.3 to 1.1±1.2, p=0.001). From the safety point of view, patients showed a slight decrease in the average value of the number of neutrophils — from (3.1±1.4)×109 to (3.0±2.0)×109 and lymphocytes — from (1.8±0,9)×109 to (1.7±0.9)×109, as well as minimal multidirectional changes in the mean values of transaminase activity — alanine aminotransferase changed from 33.9±23.6 U/L to 34.9±47.5 U/L, aspartate aminotransferase — from 40.6±49.0 U/L to 38.5±25.5 U/L. In general, the results obtained within the experience of the clinical use of baricitinib in 113 Russian patients with COVID-19 are consistent with the available data from foreign clinical studies and conﬁrm the eﬃcacy and safety of baricitinib.